REGLES TRADITIONNELLES DE PROTECTION DES RESSOURCES EN EAU DANS LE BASSIN VERSANT DE LA MEKROU (SOUS BASSIN BÉNINOIS DU FLEUVE NIGER, AFRIQUE DE L’OUEST - BOKO, MICHEL; VISSIN, EXPÉDIT WILFRID; HEDIBLE, SIDONIE CLARISSE; Ali moumouni, Bawa n’gobi (My University, 2019)
The agricultural, hunting and fishing potentials of the Mékrou watershed have favored the establishment of different socio-cultural groups that perceive water as a god's gift. And as such, it is a common good of communities. To better understand this question, the perception of the populations of the origin of the water and of the hydro-climatic variation in the basin was studied. The methodological approach used includes data collection, processing and analysis. Socio-economic surveys were conducted in selected villages on the basis of well-defined criteria. In total, 271 people were surveyed during the fieldwork that was conducted in 34 localities of the Mékrou watershed. The results of this research show that, for all the populations of the Mekrou basin, water has a cultural and cultic dimension. It would house deities. The water is sacred and its protection is through the use of these deities through invocations, the practice of rituals, cults and the introduction of prohibitions etc according to the people surveyed. In general, the perceptions of pre-colonial societies in Benin of the management and protection of water resources are mentioned in the "customary of Dahomey". Nowadays, because of the increase in the population, the frantic race for profit, the proliferation of beliefs, the disappearance of points, plans and rivers due to climate change and to anthropogenic actions, the endogenous practices of protection of water resources are becoming increasingly stale. Also, through their behavioral reflexes, the populations show that they skilfully ignore everything of the modern legal and institutional mechanism set up for the enjoyment and rational management of these water resources. The modern rules of water resources management are not, in the current state of affairs, (the illiteracy of the populations fundamentally anchored in their socio-cultural realities) will not be able to assure their real protections. So, a good protection of these resources goes through the combination of these endogenous protection strategies and the legal instruments both national and international applied with rigor.
Keywords: Mekrou; watershed; water; endogenous knowledge; integrated management.